ZONE PROXIMAL DEVELOPMENT GIVES A NEW MEANING TO THE STUDENTS’ INTELLIGENCE IN STATISTICAL METHOD LESSON - Tinungki, Georgina Maria (Universitas Papua, 2019)
Development of Zone of Proximal Development (ZPD) a learner needs guidance, help from adults or peers with a higher skill set in order of achieve a higher level of development. The level of knowledge or gradual knowledge is called by Vygotsky as scaffolding. Scaffolding means giving learners helps during the early stages of learning, then reducing the quantity of help and giving the learner opportunity to immediately take on the greater responsibility, after being able to do tasks on their own. One in the statistics Lesson program is Statistical Method, which requires high-level thinking since the students are hoped to be able to analyze statistics inference. In this case, students need help during the learning process in order to understand the concept of Statistical Method material optimally. The help could be in the form of guidance, encouragement, outlining problems into other forms that enable students to be independent. By implementing the ZPD process in the form of scaffolding stage, students are able to understand concepts of Statistical Method material optimally.